Knowledge and learning in the determination of the optimal form of firm organisation - Jenni Oksanen (The Research Institute of the Finnish Economy (ETLA), 2003)
This study examines the optimal form of a firm's organisation. Specifically, it discusses the efficient degree of labour specialisation in a firm. Specialisation of labour improves labour productivity through learning-by-doing. The problem of organisation arises, however, from the fact that the actions of specialised workers need to be coordinated in order to achieve gains from cooperation. Therefore, coordination costs may limit returns to specialisation. Moreover, changes in technology or workers' human capital may change the returns to learning in favour of less specialisation. The thesis compares theoretically the relative efficiency of organisations, which feature different degrees of labour specialisation. The comparison is made by showing how learning and communication take place in different organisational structures, and how the costs and returns to these activities vary. The optimal degree of labour specialisation under different conditions is then derived. The model of Lindbeck and Snower (2000) addresses the efficient form of work organisation in terms of the degree of labour specialisation by work task. It examines when it is worthwhile to have workers specialising by task and when they should perform multiple tasks. It finds that it is optimal for workers to perform multiple tasks only if performing different tasks is sufficiently complementary to each other. As a result, the returns to task integration outweigh the returns to specialisation. Moreover, exogenous changes in technology or human capital may change the relationship of these returns in favour of one or the other type of organisation. The second model from Greenan and Guellec (1994) compares a centralised and a decentralised organisation focusing on the coordination of learning-by-doing among workers. It takes communication costs into account because learning requires information sharing among workers. A decentralised organisation is associated with low costs of producing knowledge and high communication costs, whereas the opposite holds for the centralised organisation. It turns out that the optimal organisational form depends on the size of the labour force. Furthermore, the relative efficiency of the two organisation styles may change in favour of decentralisation when product differentiation in the economy grows. – – Tämä tutkielma käsittelee yrityksen optimaalista organisaatiomuotoa, tarkemmin ottaen optimaalista työvoiman erikoistumisastetta yrityksessä. Työvoiman erikoistuminen parantaa työn tuottavuutta tekemällä oppimisen (learning-by-doing) kautta. Työn organisoimisen ongelma on kuitenkin se, että erikoistuneiden työntekijöiden toiminta pitää koordinoida, jotta yhteistyön edut voidaan saavuttaa. Siten koordinaatiokustannukset voivat rajoittaa erikoistumisen tuottoja. Lisäksi teknologian tai inhimillisen pääoman muutokset voivat muuttaa oppimisen tuottoja tehtävien integroimisen suuntaan erikoistumisen sijaan. Tutkielmassa vertaillaan teoreettisesti erilaisten organisaatioiden suhteellista tehokkuutta sen mukaan, kuinka erikoistunutta työvoima on. Keskeisellä sijalla on se, miten oppiminen ja kommunikaatio on organisoitu erilaisissa organisaatiomalleissa ja miten oppimisen ja kommunikaation tuotot ja kustannukset vaihtelevat. Optimaalinen työvoiman erikoistumisaste eri olosuhteissa johdetaan tämän analyysin perusteella. Ensimmäinen käsiteltävä malli pohjautuu Lindbeckin ja Snowerin (2000) artikkeliin. Mallissa vertaillaan kahta organisaatiomuotoa, joissa on vastakkaiset työvoiman erikoistumisasteet. Mallissa tutkitaan sitä, milloin työntekijöiden kannattaa erikoistua tehtävien mukaan ja milloin heidän pitäisi suorittaa useampia tehtäviä. Tuloksena on se, että työntekijöiden on optimaalista suorittaa useampia tehtäviä silloin, kun nämä tehtävät ovat komplementaarisia toisilleen. Tällöin tuotot tehtävien integroimisesta ovat suuremmat kuin tuotot erikoistumisesta. Lisäksi eksogeeniset muutokset teknologiassa tai inhimillisessä pääomassa voivat muuttaa näiden tuottojen suhdetta. Toinen, Greenanin ja Guellecin (1994) malli vertaa keskitettyä ja hajautettua organisaatiota keskittyen tekemällä oppimisen koordinointiin. Mallissa huomioidaan myös kommunikaatiokustannukset, koska oppiminen edellyttää kommunikaatiota työntekijöiden välillä. Hajautetussa organisaatiossa tiedon tuotantokustannukset ovat matalat mutta kommunikaatiokustannukset korkeat. Keskitetyssä organisaatiossa tilanne on taas päinvastoin. Mallissa näytetään, kuinka optimaalinen organisaatiomuoto riippuu työvoiman koosta. Lisäksi näiden kahden organisaatiomuodon suhteellinen tehokkuus voi muuttua talouden tuotedifferentaation kasvaessa. – organisaatioteoriat ; tieto ; oppiminen ; työvoiman erikoistuminen
Keywords: D21; M54; 330; organisation theory; knowledge; learning; labour specialisation